2019
DOI: 10.1007/s00441-018-02987-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signalling and antidepressant action revisited

Abstract: Studies about the pathogenesis of mood disorders have consistently shown that multiple factors, including genetic and environmental, play a crucial role on their development and neurobiology. Multiple pathological theories have been proposed, of which several ultimately affects or is a consequence of dysfunction in brain neuroplasticity and homeostatic mechanisms. However, current clinical available pharmacological intervention, which is predominantly monoamine-based, suffers from a partial and lacking respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 197 publications
1
49
0
Order By: Relevance
“…NO is a gaseous neurotransmitter that governs multiple physiological functions in the CNS. NO is synthesized by NOS, which has three isoforms, namely, nNOS, iNOS, and eNOS, and all three NOS isoforms exist in the CNS and affect cell signaling in brain (29). Evidence has shown that deficits in NOS activity are associated with the neurobiology of MDD (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO is a gaseous neurotransmitter that governs multiple physiological functions in the CNS. NO is synthesized by NOS, which has three isoforms, namely, nNOS, iNOS, and eNOS, and all three NOS isoforms exist in the CNS and affect cell signaling in brain (29). Evidence has shown that deficits in NOS activity are associated with the neurobiology of MDD (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that deficits in NOS activity are associated with the neurobiology of MDD (30,31). Especially for nNOS, studies have shown that dysfunction of nNOS in the paraventricular hypothalamic nucleus, locus coeruleus, mPFC, and hippocampus, is related to MDD (29,32,33). Besides, iNOS also is involved in stress-triggered depression, as iNOS derived NO and iNOS mRNA levels increased in the cortices of depression animal model (34).…”
Section: Discussionmentioning
confidence: 99%
“…Acute stress triggers a complex response involving the synthesis and release of mediators such as corticoids, glutamate and NO, which can acutely alter gene expression as well as induce long-term molecular and behavioral changes (Popoli et al, 2011;Joca et al, 2019). The increase in NO and/or reactive oxygen species (ROS) can directly impact gene expression (Riccio et al, 2006;Lee et al, 2009;Nott & Riccio, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…NO plays an important role in the mechanisms of neuroplasticity and the neurobiology of depression. Therefore, maintaining NO signaling, counteraction of NO overproduction, and oxidative damage may be essential factors in antidepressant therapy [209]. In a model of depression induced by estrogen withdrawal (E2) under hormone-stimulated pregnancy, an increase in the immobilization time in the forced swim test and tail suspension test of ICR mice was combined with a decrease in the levels of nNOS, NO, and p-CREB in the hippocampus.…”
Section: Glutamatergic Neurotransmissionmentioning
confidence: 99%